[Rezension von: Duncan Hardy, Associative political culture in the Holy Roman Empire: upper Germany, 1346-1521] - Peltzer, Jörg (The American historical review, 2020)
Less convincing is his claim to reconceptualize the Holy Roman Empire. Scholars working on the late medieval Empire will hardly be surprised by Hardy’s findings and positions. Indeed, experts on the thirteenth century will wonder why this crucial period in shaping associative behavior in the Empire hardly features in his work. But there is only so much one can do within the framework of a doctoral thesis. Concerning the period examined in this book, it is possible, perhaps even necessary, to take a different view from Hardy’s on the current state of research. The rich scholarship from the past two decades on courts and assemblies, for example, is based on the understanding of the great significance of associative political culture. It is true—these works also take into account the hierarchical nature of this culture, but this only shows that associative behavior and the formation of hierarchy go hand in hand. These studies do by no means bark up the wrong tree; they simply develop a slightly different and, one might even argue, a more comprehensive perspective on how the social and political order of the late medieval Empire took shape. Therefore, it is not surprising that one of Hardy’s concluding remarks stating that “the Empire as a whole was the only political framework which functioned convincingly and consistently as an overarching governmental unit in German-speaking Europe” (261), is not revolutionary, but fully in line with current scholarship. As a shortcut to and assessment of the scholarship on the late medieval Empire, this book should therefore be treated with caution. It does not release one from reading the mostly German literature. However, as a guide to forms of associative political behavior and their significance for the Empire, this is a very useful book. This is no small achievement.